Clinicopathological features and resistance mechanisms in HIP1‐ALK‐rearranged lung cancer: A multicenter study. Issue 4 (1st November 2021) - Kang, Jin; Deng, Qiu‐Mei; Peng, Kai‐Cheng; Li, Peng; Zhu, Bao‐Ting; Wang, Pan; Chu, Xiang‐Peng; Zhong, Wen‐Zhao; Chen, Hua‐Jun; Wang, Wen‐Xian; Chen, Hua‐Fei; Rao, Chuang‐Zhou; et al.
Abstract: Anaplastic lymphoma kinase (ALK)‐rearranged non‐small cell lung cancer (NSCLC) respond well to ALK tyrosine kinase inhibitors (TKIs), and echinoderm microtubule‐associated protein‐like 4 ( EML4 )‐ ALK ‐rearranged NSCLC accounts for the majority of those patients. However, few studies have evaluated ALK‐TKIs treatment for patients with huntingtin‐interacting protein 1 (HIP1)‐ALK fusions. This retrospective study evaluated the clinicopathological characteristics, genomic features, response to ALK‐TKIs, and resistance mechanisms in 11 cases with HIP1‐ALK fusions from five Chinese centers. Patients who received crizotinib at the Chinese centers had an objective response rate of 90% [9/10 cases, 95% confident index (CI): 54.1%–99.5%], median progression‐free survival of 17.9 months (95% CI: 5.8–NA months), and median overall survival of 58.8 months (95% CI: 24.7–NA months). One patient who received first‐line lorlatinib treatment achieved partial response for > 26.5 months. Despite the small sample size, HIP1‐ALK (H21:A20) variant was the most common variant (four of 11 cases, 36.4%) and associated with better outcomes. Among the 11 cases, there were eight patients having available specimens for genetic testing before ALK‐TKIs treatment and four patients undergoing biopsy after ALK‐TKIs failure. The most common coexisting gene was TP53 among 11 patients and two of four patients after crizotinib failure harbored acquired ALK mutations (e.g., L1152V/Q1146K and L1196M). Brigatinib treatment appeared to be effective for a patient who failed crizotinib treatment because of the L1152V/Q1146K mutations, which might be related to increased binding affinity to these mutants. Although HIP1‐ALK‐ rearranged NSCLC appears to initially respond well to ALK‐TKIs, crizotinib resistance may be correlated with the AKAP9‐BRAF fusion, ALK compound mutations (L1152V/Q1146K), and the ALK L1196M mutation. Larger studies are needed to evaluate the significance of HIP1‐ALK ‐rearranged NSCLC.